Growth Coordination Between Butyrate-Oxidizing Syntrophs and Hydrogenotrophic Methanogens - Cong, Shuqi; Xu, Yiqin; Lu, Yahai (Frontiers in Microbiology, 2021)
Syntrophy is a thermodynamically required mutualistic cooperation between fatty acid oxidizing bacteria and methanogens that plays the important role in organic decomposition and methanogenesis in anoxic environments. In this study, three experiments were conducted to evaluate the cell-to-cell interaction in a thermophilic coculture consisting of Syntrophothermus lipocalidus and Methanocella conradii and a mesophilic coculture consisting of Syntrophomonas wolfei and Methanococcus maripaludis. Firstly, syntrophs and methanogens were inoculated at different initial cell ratio to evaluate the growth synchronization. The quantitative PCR analysis revealed that the organism with a lower relative abundance at the beginning always grew faster and the cell ratio converged over time to relative constant values in both the thermophilic and mesophilic cocultures. Next, the intermittent ultrasound and constant shaking treatments were used to evaluate the influence of physical disturbance on microbial aggregation in the mesophilic coculture. The fluorescence in situ hybridization and scanning electron microscopy revealed that the tendency of syntrophic aggregation was not affected by the physical disturbances, although the activity was slightly depressed. Syntrophomonas were dominated in the initial microbial aggregates, which however did not grow until Methanococcus were attached and increased to a significant extent, indicating the local growth synchronization during the formation and maturation of syntrophic aggregates. Lastly, microfluidic experiment was conducted, which revealed that no matter where Syntrophomonas or Methanococcus was loaded first, the second organism preferred moving to the place where the first organism was located, suggesting the cell-to-cell attraction between Syntrophomonas and Methanococcus. Collectively, our study demonstrated the growth synchronization and cell-to-cell attraction between the butyrate-oxidizing bacteria and methanogens for optimizing the syntrophic cooperation.